Genetic variants of Plasmodium falciparum infective Anopheles gambiae s.l. at a rural community in southwest Nigeria (2009)
During studies on the epidemiology of malaria at a rural community, Igbo-Ora, Southwest Nigeria, genotyping of Plasmodium falciparum extracted from infective Anopheles gambiae s.l. was undertaken. Circumsporozoite (CSP) ELISA was used on crushes from head-thorax for DNA extraction and PCR amplification for the determination of P. falciparum genotypes on merozoite surface protein-I and 2 (MSP-I & 2). Of the 65 infective anophelines, P. falciparum genotypes were positively identified in 41. Mono-infections constituted 73.4% of all infections; the dominant mono-infections on MSP-1 and MSP-2 were MAD20 (18) and ICI (09) respectively; the rare RO33 (01) was recorded. Double infections were 20.20% (09) with both markers, while only one triple infection was observed on MSP-1. An anopheles was found with two double infections, one on each of the two blocks. Eight of the 12 multiple infections were on MSP-1, five on both MSP-1 and MSP-2. In addition to the multiplicity of proteins in these vectors, size polymorphism was observed in alleles, indicating vector/parasite interactions and environmental variations. These results were compared to those from human sera.